General Reports of the XVIIIth Congress of the International Academy of Comparative Law/Rapports Généraux du XVIIIème Congrès de l’Académie Internationale de Droit Comparé
X, 704 p.
Keywords: This title presents twenty-nine topics, prepared by leading scholars in more than 20 countries, providing a comparative analysis of cutting-edge legal topics of the 21st century. Considering topics of vital moment to contemporary legal scholars, the title includes pieces on Surrogate Motherhood, The Balance of Copyright in Comparative Perspective, International Law in Domestic Systems, Constitutional Courts as "Positive Legislators," Same-sex Marriage, Climate Change and the Law, The Regulation of Private Equity, Hedge Funds, and State Funds, and Regulation of Corporate Tax Evasion. Each chapter surveys legal developments in the U.S. and Canada, Europe, Asia, Latin and South America, Africa, and the Middle East in a format that permits the reader easy access to similarities and differences in the approaches of the selected national regimes. This comprehensive volume tells the story of parallel trends in the evolution of legal doctrine despite jurisdictional, cultural, and political barriers. While each of the covered countries stands alone as a sovereign, in a technologically advanced world their disparate systems nonetheless have converged to adopt comparable strategies in dealing with complex legal issues. The volume is a critical addition to the library of any scholar hoping to keep abreast of the major trends in contemporary law.